2008
DOI: 10.3748/wjg.14.6458
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma: A compact review of the literature

Abstract: intraductal high-intensity ultrasonography and chemotherapy-impregnated plastic biliary endoprosthesis are important steps in the palliative management of extrahepatic CCs. Radiofrequency and chemo-embolization methods are also applicable for intra-hepatic CCs as palliative modes of treatment. We need more prospective randomized controlled trials to evaluate the role of the new emerging therapies for CC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
103
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 86 publications
0
103
0
5
Order By: Relevance
“…Although cholangiocarcinoma is a relatively rare hepatobiliary cancer, the incidence and mortality of cholangiocarcinoma have increased worldwide in recent years (1)(2)(3). In fact, intrahepatic cholangiocarcinoma is the second most common liver cancer, accounting for 10% to 15% of all primary liver malignancies (4).…”
Section: Introductionmentioning
confidence: 99%
“…Although cholangiocarcinoma is a relatively rare hepatobiliary cancer, the incidence and mortality of cholangiocarcinoma have increased worldwide in recent years (1)(2)(3). In fact, intrahepatic cholangiocarcinoma is the second most common liver cancer, accounting for 10% to 15% of all primary liver malignancies (4).…”
Section: Introductionmentioning
confidence: 99%
“…Intrahepatic cholangiocarcinoma (ICC), the second most common primary hepatobiliary cancer globally, is a major cause of cancer-related deaths and shows no indication of a decrease in mortality rate (Khan et al, 2005;Ustundag and Bayraktar, 2008;Mosconi et al, 2009). Although the incidence of ICC had been primarily associated with developing countries, ICC is now increasing in developed countries, especially in the United Kingdom and Japan (Kato et al, 1990;TaylorRobinson et al, 1997;McLean and Patel, 2006;West et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…8,9) Several epidemiological studies have shown that the incidence and mortality rates of CCA are increasing worldwide. [10][11][12] Biliary tract tumors remain a challenge to treat and manage due to their poor sensitivity to conventional therapies and discouraging treatment options. 13) In fact, radical surgery, the only effective treatment, is applicable in a minority of patients due to the common late clinical presentation and diagnosis of this tumor.…”
mentioning
confidence: 99%